In the kingdom of “tortelli” (ravioli-like pasta) plant poisoning is still a threat. A case report of near-fatal poisoning from Digitalis Purpurea accidentally confused with Borago Officinalis. - Bonfanti, Laura; Lippi, Giuseppe; Ciullo, Irene; Robuschi, Fiorenza; Aloe, Rosalia; Tarasconi, Sara; Vassallo, Riccardo; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2017)
A 58 years healthy old woman was admitted to the Emergency Department (ED) with cardiac arrest due to ventricular fibrillation (VF). Appropriate cardiopulmonary resuscitation (CPR), multiple DC shocks and oro-tracheal intubation (OTI) were effective to induce recovery of spontaneous circulation (ROSC). After ROSC was achieved, the electrocardiogram (ECG) showed an idio-ventricular rhythm with atrioventricular dissociation. A transcutaneous pacing was hence applied and the patient was administered with isoproterenol. Simultaneously, her husband was evaluated in the ED for gastrointestinal symptoms occurred after assumption of home-made “tortelli” (ravioli-like pasta) stuffed with cheese and leaves of a plant which they supposed to be borage two days before admission. Borage, during the non-flowering seasons, can be easily confused with foxglove (Digitalis spp.), and this was the main clue to suspect poisoning. Both patients were given DigiFab®, a sheep antibody fragment with high affinity for digoxin. The woman was then admitted in intensive care unit (ICU), where a rapid clinical improvement occurred, thus allowing discharge in a few days. The husband was instead discharged from the ED after clinical observation and ECG monitoring. In both cases, a significant plasma concentration of digoxin could be measured.